1997
DOI: 10.1124/mol.51.6.1024
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Substrates and Antagonists Cluster into Two Distinct Groups

Abstract: To gather further insight into the interaction between P-glycoprotein (Pgp) and its substrates, 167 compounds were analyzed in multidrug resistant human colon carcinoma cells. These compounds were selected from the National Cancer Institute Drug Screen repository using computer-generated correlations with known Pgp substrates and antagonists. The compounds were prospectively defined as Pgp substrates if cytotoxicity was increased > or =4-fold by the addition of cyclosporin A (CsA) and as Pgp antagonists if inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(132 citation statements)
references
References 40 publications
2
129
0
Order By: Relevance
“…Many substrates and modulators of P-glycoprotein have been shown to stimulate or inhibit vanadate-sensitive associated ATPases (31,40,41). As a consequence we examined that characteristic for BPA over a wide concentration range (100 nM to 10 μM).…”
Section: Discussionmentioning
confidence: 99%
“…Many substrates and modulators of P-glycoprotein have been shown to stimulate or inhibit vanadate-sensitive associated ATPases (31,40,41). As a consequence we examined that characteristic for BPA over a wide concentration range (100 nM to 10 μM).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to inhibit photoaffinity labeling has frequently been used as an indicator of whether a particular drug interacts with Pglycoprotein (26,27). Therefore, to demonstrate the binding of the anthracycline derivatives to P-glycoprotein and to determine whether differences in azidopine competition could be identified between cytotoxic and noncytotoxic anthracycline derivatives, photolabeling experiments were performed on CH R B30 plasma membrane vesicles in which about 15% of the protein is P-glycoprotein.…”
Section: Inhibition Of [ 3 H]azidopine Photolabeling Of P-glycoproteimentioning
confidence: 99%
“…After intracellular bioactivation (Furumai et al, 2002;Xiao et al, 2003), FK228 specifically inhibits class I HDAC enzymes (Furumai et al, 2002), and results in the induction (e.g., p21) or suppression (e.g., c-Myc) of various target genes (Sandor et al, 2000b). An in vitro screening conducted at the National Cancer Institute indicated that FK228 is an MDR1 (P-glycoprotein, ABCB1) substrate (Scala et al, 1997). Recently, we have shown that FK228 is a substrate of multidrug resistance-associated protein 1 (MRP1 or ABCC1) .…”
mentioning
confidence: 99%